Maternal insulinemic and inflammatory dietary patterns and risk of child neurodevelopmental delay. - Wang, Haixia; Zu, Ping; Yin, Wanjun; Zhang, Lei; Ruan, Liang; Chen, Xianxia; Zhu, Peng (European Journal of Nutrition, 2025)
Purpose: Our aim was to assess the risk of higher insulinemic, inflammatory, and hyperglycemia potential in the diet during pregnancy with child neurodevelopmental delay. Methods: We enrolled 7,438 pregnant women participating in a prospective cohort study. The food frequency questionnaire was used to evaluate the empirical dietary index for hyperinsulinemia (EDIH), empirical dietary inflammatory pattern (EDIP), glycemic index (GI), and glycemic load (GL) during mid-pregnancy. Child neurodevelopmental assessment was conducted at 6–36 months postpartum using the Denver Developmental Screening Test-II (DDST-II) scale, and the Gesell Developmental Diagnosis Scale (GDDS) was administered to assess children who did not meet the criteria for passing the DDST-II screening. Results: We documented 540 incident child neurodevelopmental delay cases over 7,438 pregnant women (median follow-up: 2 years). Pregnant women exhibiting the high levels of hyperinsulinemic or proinflammatory components, or GI encountered an elevated risk of child neurodevelopmental delay; HRs (95% CI) comparing highest to lowest dietary index quintiles were EDIH 1.48 (1.07,2.04; P trend = 0.017), EDIP 1.39 (1.05,1.84; P trend = 0.019) and GI 1.36 (1.02,1.81; P trend = 0.038). In sex-stratified analyses, these results remained significant only in boys (P trend = 0.018 for EDIH, P trend = 0.028 for EDIP, P trend = 0.029 for GI). The performance of combined model of EDIH and EDIP for boys is comparable to that of the combined model of EDIH, EDIP, and GI to assess the risk of neurodevelopmental delay (AUC [area under curve] 0.801 vs. AUC 0.830). Both values are higher than the AUC values achieved by models using either set of indicators individually. Conclusion: Our findings suggest that maternal consumption of diets with high insulinemic, inflammatory, or glycemic index properties may be associated with neurodevelopmental delays in children, particularly in boys. Higher insulinemic and inflammatory potentials in maternal diet may forecast neurodevelopmental delay in boys.